How Chimeric Animal Research Impacts Animal Welfare: A Conversation with Animal Welfare Experts. (9th December 2022) - Craig, Kaitlynn P.
Abstract: In this conversation, four experts in animal research oversight—Christopher Stodgell, Lori Hill, Robert Kesterson, and Angelika Rehrig—discuss the complexities of stem cell‐based chimeric animal experiments, especially in relation to traditional animal welfare practices. Each expert shares their experiences and suggestions for how best to conduct chimeric animal research, including discussing the importance of communication and collaboration between experts in animal behavior and welfare and the investigators conducting or proposing chimeric research studies .